Conectores adversativos em textos jornalísticos sobre futebol: análise funcionalista em perspectiva histórica. - Brito, Isabel Pauline Lima de (2016)
This work is the analysis of adversative connectors which are present in the newspaper articles about soccer, in Pernambuco. To execute this, is has been used a corpus with data from the early XX century and the early XXI century. In all, sixty articles were analyzed, thirty for each time sample, in a total of a hundred and fifteen adversative items found. The study of function behavior of the items is observed by the application of functionalist theoretical support: markedness principle, iconicity principle and prototypes theory. We follow this theoretical perspective based on the studies of Givón (1990 and 1995), Hopper and Traugott (1993 and 2003), Neves (2000), Castilho and Elias (2012), Furtado da Cunha et al (2013). The analysis uses, in contrast, the consultation with traditional grammarians, as Almeida (1962), Melo (1978), Cunha (1986), Cegalla (1989), Bechara (2009), and others. Among the results, it has been verified that the item ‘mas’ has been presented as the prototypical of adversity, remaining as the most frequent in the two time samples of the research. This shows the prototypical value of the item in this function, although there has been insertion of it in contexts of innovative uses. Furthermore, it is observed that the traditional grammar hasn’t updated the list of adversative conjunctions once they haven’t adopted perspectives of observing the item in use situation. They have disregarded the language change process.